2000
DOI: 10.1007/s002100000316
|View full text |Cite
|
Sign up to set email alerts
|

Modes of allosteric interactions with free and [ 3 H] N -methylscopolamine-occupied muscarinic M 2 receptors as deduced from buffer-dependent potency shifts

Abstract: Muscarinic M2 acetylcholine receptors contain an allosteric site that is probably located at the entrance of the ligand binding pocket above the orthosteric binding site. With the orthosteric area not occupied, allosteric agents might gain access to this site. The interaction of allosteric agents with orthoster-occupied receptors is known to depend on the buffer conditions in an alloster-specific fashion. Utilizing the buffer-dependent potency shift as an indicator, we aimed to find out for two rod-like shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…However, tacrine and Duo3 also slow down the dissociation rate of [ 3 H]NMS with slope factors greater than 1 (Table 3, Fig. 7) (Potter et al, 1989;Trä nkle and Mohr, 1997;Schröter et al, 2000). In this experiment, the orthosteric site is occupied by [ 3 H]NMS; therefore, the effects causing the slope factors to be greater than 1 are allosteric in nature and independent of occupancy of the orthosteric site.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, tacrine and Duo3 also slow down the dissociation rate of [ 3 H]NMS with slope factors greater than 1 (Table 3, Fig. 7) (Potter et al, 1989;Trä nkle and Mohr, 1997;Schröter et al, 2000). In this experiment, the orthosteric site is occupied by [ 3 H]NMS; therefore, the effects causing the slope factors to be greater than 1 are allosteric in nature and independent of occupancy of the orthosteric site.…”
Section: Discussionmentioning
confidence: 78%
“…If AF-DX 384 were purely allosteric, as proposed for the analog AF-DX 116 (Lanzafame et al, 2001) Fig. 7) (Potter et al, 1989;Schröter et al, 2000). This might suggest simultaneous and positively cooperative binding of these ligands to both the orthosteric and allosteric sites.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, affinities for the free receptor cannot be extracted from these data. There are, however, some indications that suggest that there is a common binding mode for allosteric ligands at the free and NMSliganded receptors (Ellis and Seidenberg, 2000;Schröter et al, 2000). Because [ 3 H]NMS dissociated much more rapidly from the M 2 subtype than from M 5 , one could argue that high-affinity binding of the allosteric ligand is associated with a fast dissociation and low-affinity binding with slow dissociation of [ 3 H]NMS.…”
Section: Discussionmentioning
confidence: 99%
“…One key observation supporting this concept is that certain indolocarbazole (Lazareno et al, 2000) and androstane (Lazareno et al, 2002) derivatives are predicted to bind to a nonorthosteric site different from that recognized by other allosteric muscarinic ligands such as gallamine or strychnine. Moreover, several allosteric muscarinic ligands, including the acetylcholinesterase inhibitor tacrine (Potter et al, 1989) and the bis-pyridinium derivative Duo3 (Trä nkle and Mohr, 1997;Schröter et al, 2000), have been identified that, in contrast to conventional allosteric muscarinic ligands, display concentration-effect curves with slope factors Ͼ1. The complex binding properties of Duo3 suggested that this ligand, similar to the above-mentioned indolocarbazole and androstane derivatives, may interact with a second allosteric binding site (Trä nkle and Mohr, TABLE 1 Major advantages associated with the potential therapeutic use of GPCR ligands acting on allosteric sites…”
mentioning
confidence: 99%